2018
DOI: 10.18034/gdeb.v7i2.725
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Optimization Models for Supply Chain Management: Integrating Uncertainty into Decision-Making Processes

Dileep Reddy Goda,
Sridhar Reddy Yerram,
Suman Reddy Mallipeddi

Abstract: This study examines how supply chain management can use stochastic optimization models to overcome the problems associated with decision-making uncertainty. The study's primary goals are reviewing the literature on stochastic optimization models in supply chain management, gaining a thorough grasp of their applications, and evaluating how well they integrate uncertainty into decision-making processes. The method includes a comprehensive assessment of the current literature body, including scholarly journals, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Blockchain offers many ways to improve financial security throughout digital transformation. Blockchain protects financial systems from cyberattacks, fraud, and data breaches through decentralization, immutable ledger, cryptographic security, smart contracts, transparency, and interoperability (Goda et al, 2018). Financial institutions may usher in a new era of digital finance by using blockchain technology to improve security, efficiency, and confidence in financial transactions.…”
Section: Blockchain Solutions For Financial Securitymentioning
confidence: 99%
“…Blockchain offers many ways to improve financial security throughout digital transformation. Blockchain protects financial systems from cyberattacks, fraud, and data breaches through decentralization, immutable ledger, cryptographic security, smart contracts, transparency, and interoperability (Goda et al, 2018). Financial institutions may usher in a new era of digital finance by using blockchain technology to improve security, efficiency, and confidence in financial transactions.…”
Section: Blockchain Solutions For Financial Securitymentioning
confidence: 99%
“…Mechanisms to identify and reduce biases are incorporated into ADRSoB, including diversity-promoting goals, fairness-aware learning algorithms, and routine audits of algorithmic outputs. Furthermore, stakeholders may comprehend the underlying decision-making processes and proactively uncover biases using transparent and interpretable AI models (Goda et al, 2018).…”
Section: Selection Of Ai Techniquesmentioning
confidence: 99%
“…AI-driven HR practices must include justice, according to the literature. Algorithmic biases from biased training data or incorrect algorithm design might discriminate in HR decisionmaking, disadvantage demographic groups, or perpetuate structural injustices (Goda et al, 2018). Studies have shown that AI-powered resume screening systems penalize female and minority candidates.…”
Section: Fairness Considerations In Ai-driven Hrmentioning
confidence: 99%